Effects of Boiled Tomato Waste Utilization in the Diet on Serum Lipid Profile and Egg Quality of Laying-hens - Mahata , Maria E.; Rizal, Yose; Ardi; Hermansyah, Dedek; Nurhuda, Gina A. (International Journal of Poultry Science, 2016)
Objective: An experiment had been conducted to study the effects of boiled tomato waste utilization in the diet on the serum lipid profile: total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL) and the egg quality (egg yolk cholesterol, egg yolk lipid and egg yolk color index) of 200 Isa Brown laying-hens of 60 weeks-old fed diet containing boiled tomato waste powder and to determine the appropriate level of boiled tomato waste in the diet. Materials and Methods: The experiment was performed in a completely randomized design with five different levels of boiled tomato waste powder in diets (0, 3, 6, 9 and 12%) as treatments and each treatment was replicated four times. Measured variables were total cholesterol, LDL and HDL of blood serum and total cholesterol, fat contents of egg yolk as well as egg yolk color index of laying-hens. Results: The experiment showed that the total cholesterol, LDL and HDL of laying-hen’s blood serum and fat content of egg yolk was not affected (p>0.05) by different levels of boiled tomato waste powder in diets, while the egg yolk total cholesterol and egg yolk color index were significantly influenced (p<0.05). The increase in the level of boiled tomato waste powder in the diet reduced the total cholesterol in egg yolk but increased the egg yolk color index. Conclusion: The inclusion of 12% boiled tomato waste powder in laying-hen’s diet was the best level for lowering egg yolk total cholesterol and improving egg yolk color index.